PENERAPAN VIRTUAL REALITY MENGGUNAKAN METODE RAPID APPLICATION DEVELOPMENT PADA MEDIA PEMBELAJARAN PENGENALAN SATWA ENDEMIK TAMAN NASIONAL UJUNG KULON - Ratna Salkiawati; Hendarman Lubis; Markus Ade Putra (JURNAL REKAYASA INFORMASI, 2022)
This research is about making an android-based virtual reality application as a learning medium for the introduction of endemic animals in Ujung Kulon National Park. Currently, the learning process for the introduction of endemic animals is still using 2D images so that it does not attract students' interest in recognizing endemic animal species. This virtual reality application aims to provide an experience for students to see the endemic animals of Ujung Kulon National Park in reality without having to be on location, students also easily get information about endemic animals of Ujung Kulon National Park. The activity of making virtual reality applications is a supporting media that can be used in the teaching and learning process that is easy to understand and increases the interest and interest of students to learn about the introduction of endemic animals to Ujung Kulon National Park. In designing the application, the method used in this study uses the RAD (Rapid Application Development) method, which is an object-oriented system development method to shorten the time of system development. the stages consist of business modelling, data modelling, process modelling, application generation, testing and implementation. Making 3D applications using virtual reality based on Android uses the Java programming language, and Kotlin. This study resulted in a learning media application for the introduction of endemic animals in Ujung Kulon National Park using android-based virtual reality.